Correlation between physical characteristics and plant composition of home gardens in Bandung City, West Java, Indonesia - SALSABILA LARASWARI; INDRI WULANDARI; TEGUH HUSODO; OEKAN S. ABDOELLAH; CIKA ASTI AMALIA; MUHAMMAD RIFQI FAWWAZ; SYAHARBANU MEHRI AZADI; SHOFI SITI FARHANIAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Laraswari S, Wulandari I, Husodo T, Abdoellah OS, Amalia CA, Fawwaz MR, Azadi SM, Farhaniah SS. 2024. Correlation between physical characteristics and plant composition of home gardens in Bandung City, West Java, Indonesia. Biodiversitas 25: 3051-3060. Green open space in urban settings provides various benefits to city residents, yet the increase in urban population indirectly results in a decrease in urban green space. Home gardens can expand urban green space to complement public areas but are often overlooked. This research examines the physical characteristics (area size, shape, and zoning) and plant composition of home gardens in Bandung City, West Java, Indonesia, as well as the correlation between both aspects. This research examined extensive data collection from a densely populated urban area, a context rarely explored but highly relevant in recent urban development. Data was collected in five housing complexes in the Rancasari Sub-district, with 514 home gardens, and correlation analysis was performed using Canonical Correspondence Analysis (CCA). The result showed that 92.2% of the home gardens had very narrow areas with 2-53m2. The shape of the home garden was dominated by strips, with 66% and 94% of home gardens having front zoning. Across the sampled home gardens, there were 1054 species from 141 families, with a total of 32,967 individuals. Araceae was the most commonly found family with 100 species and Sri Rejeki (Aglaonema commutatum Schott) had the largest number of individuals. Most of the home garden plants were ornamental plants due to their attractive morphology, making them relatively homogeneous within 95% of the home gardens. The presence of ornamental plants was the least influenced by physical characteristics, while medicinal and spice plants can be grouped together as they were more affected by the area size and less by the zone and shape. Edible plants were the most influenced by all physical characteristics, particularly the zone. This study provides new insights into urban ecology, offering valuable information for homeowners, developers, and policymakers to enhance the role of home gardens as private green spaces.